The curious history of the heart a cultural and scientific journey - Figueredo, Vincent M. (New York Columbia University Press, 2023)
This book traces the evolution of our understanding of the heart from the dawn of civilization to the present. Vincent M. Figueredo-an accomplished cardiologist and expert on the history of the human heart-explores the role and significance of the heart in art, culture, religion, philosophy, and science across time and place
Cover -- Title Page -- Copyright -- Dedication -- Contents -- Introduction -- I The Ancient Heart -- 1 The Heart Means Life -- 2 Heart and Soul -- 3 The Heart and God -- 4 An Emotional Heart -- 5 Ancient Understanding of the Physical Heart -- 6 Ancient Heart Disease -- II The Heart Goes Into the Darkness and Comes Out in the Light -- 7 The Dark Ages -- 8 The Islamic Golden Age -- 9 The Viking Cold Hjarta -- 10 American Heart Sacrifice -- 11 The Heart Renaissance -- 12 Hither and Thither -- III heART -- 13 The Heart in Art -- 14 The Heart in Literature -- 15 The Heart in Music -- 16 Heart Rituals -- IV Heart 101 -- 17 The Pump -- 18 Heart Anatomy -- 19 Heart Sounds -- 20 The Color of Blood -- 21 The Heart's Electrical System -- 22 What Is an EKG? -- 23 What Is Blood Pressure? -- 24 What Is Heart Failure? -- 25 What Is "Having a Coronary"? -- 26 Sex, Race, and Ethnicity in Heart Disease -- 27 Sudden Death of an Athlete -- 28 The Word Heart -- V The Modern Heart -- 29 Enlightenment and the Age of Revolution -- 30 The Twentieth Century and Heart Disease -- 31 Aspirin -- 32 The Twentieth Century and Heart Surgery -- 33 The Heart Now -- 34 The Broken Heart Syndrome -- 35 The Heart-Brain Connection -- 36 The Future Heart
Includes bibliographical references and index
Description based on print version record
eBooks on EBSCOhost
Keywords: Heart -- Popular works; Cardiology -- History; Heart; Heart; Cardiology -- history; Cœur -- Ouvrages de vulgarisation; Cardiologie -- Histoire; Cœur; MEDICAL / Cardiology; Cardiology; Heart; Electronic books; History; Popular works